2513. The Utility of Next-Generation Sequencing for Detection of Causative Viruses in Sera of Patients With Acute Myocarditis. (26th November 2018) - Takeuchi, Suguru; Kawada, Jun-Ichi; Okuno, Yusuke; Horiba, Kazuhiro; Suzuki, Takako; Torii, Yuka; Yasuda, Kazushi; Numaguchi, Atsushi; Kato, Taichi; Ito, Yoshinori
Abstract: Background: Myocarditis is an inflammatory disease of the myocardium with a wide range of clinical presentations, occasionally leading to cardiac dysfunction and heart failure. Although viral infections are considered to be the most common etiology of myocarditis, identification of the causative virus is still challenging. Recently, next-generation sequencing (NGS) has been applied in the diagnosis of infectious diseases. The aim of this study was to evaluate the utility of NGS for detection of causative viruses in sera of patients with acute myocarditis. Methods: Twelve pediatric and five adult patients hospitalized for acute myocarditis were included in this study. Serum samples before initiation of treatment were collected in the acute phase and analyzed with NGS-based approach. To detect pathogen-derived sequencing reads, we performed DNA and RNA sequencing for each sample. Results: An average of 20, 062, 443 and 19, 506, 189 total reads were obtained in DNA and RNA sequencing libraries, respectively. Viral sequence reads were detected in 7 (41%) of the 17 myocarditis patients. Substantial sequence reads of GB virus C (GBV-C) reads were detected from one patient by RNA sequencing; however, its pathogenicity to human is unknown. Detection of Epstein–Barr virus, human parvovirus B19, and respiratory syncytial virus reads by NGS was consistent with PCR or antigen test results. Conversely, the number of detected virus-derived reads was small in most cases. No significant bacterial or fungal reads other than normal bacterial flora was detected. Conclusion: NGS-based approach may have potential to detect the causative viruses and contribute to clarification of the etiology of acute myocarditis. Disclosures: All authors: No reported disclosures.